(untitled) (Journal of Modern Mechanical Engineering and Technology, 2025)
The results of tests under boundary friction conditions are present detonation coatings Zr-Al-B in a wide range of changes in friction conditions. The obtained results were compared with the parallel tested coatings based on tungsten carbide type WK-15, also with samples of 30HGSNA steel and BrOCS6-6-3 bronze. The qualitative and quantitative composition of surface layers participating in boundary friction conditions was assessed using modern physical methods of analysis. Profilograms and microphotographs of friction surfaces of amorphous-crystalline coatings are presented, showing that under boundary friction conditions, coating samples are smoothed, which leads to a decrease in roughness. Installed the presence of the formation of solid solutions of oxygen interstitialization in zirconium, which corresponds to the formation of secondary structures of the first type on friction surfaces, the characteristic feature of which is their surface localization, ultra-dispersed structure, the ability to minimize destruction and screen unacceptable adhesive phenomena. Using Auger electron microscopy, it was confirmed that oxygen completely replaces sulfur in surface structures. It is shown that the studied detonation coatings Zr-Al-B, developed for practice, have high tribotechnical characteristics in the entire range of tests under boundary friction conditions. At the same time, as a result of studies of the mechanism of tribochemical transformations of hydrocarbons and the properties of transformed surface films, it was established that they retain lubricating properties and provide high antifriction characteristics of the friction system in the entire wide range of changes in boundary friction conditions.